Outcome of Scleral Buckling Surgery in Rhegmatogenous Retinal Detachment - Hossain, MI; Hasan, MK; Ali, MSM (Journal of Armed Forces Medical College, Bangladesh, 2010)
A longitudinal study was carried out in the vitreo-retina clinic of the National Institute of Ophthalmology and Hospital (NIO&H) on 30 eyes of 25 patients who were treated with scleral buckle (SB) surgery during the period of October 2004 to September 2005 of either sex. The aim of this study was to determine the outcome of SB surgery in Rhegmatogenous retinal detachment (RRD). The main entry criteria for this study were primary RRD treated with SB and for which 12 weeks of follow-up were available. The eyes with proliferative vitreoretinopathy or with history of SB surgery, vitrectomy, posterior segment open-globe trauma or significant concurrent eye disease e.g. amblyopia, macular disease etc were excluded from this study. Overall twenty-four eyes (80%) achieved retinal reattachment with one SB procedure (encircling or segmental); the median 12-week visual acuity was 6/12. Three additional eyes (10%) achieved retinal reattachment with one vitreoretinal procedure; the median 12-week visual acuity was 6/9. Three eyes (10%) never achieved retinal reattachment despite one additional vitreoretinal procedure, and 12-week visual acuity was no perception of light. It can be concluded that SB for primary RRD achieves anatomical efficacy and preservation of central vision in the majority of eyes. Key words: Scleral buckle; Rhegmatogenous retinal detachment outcome. DOI: 10.3329/jafmc.v6i1.5987 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.21-24